The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/1529-0131(199911)42:11<2281::aid-anr4>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation in refractory rheumatoid arthritis: Sustained response in two of four patients

Abstract: In this series, autologous HSCT was safe and effective in inducing major clinical response and maintained significant benefit for 2 patients at 9 months and 20 months posttreatment, respectively. Sustained response did not occur for 2 of 4 patients. A regimen dose-response effect may exist, but the addition of TBI did not prevent disease relapse for 1 of the patients. More aggressive T cell depletion of the autograft, use of a myeloablative regimen, or use of an allograft may be necessary to decrease relapse r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 16 publications
1
41
0
3
Order By: Relevance
“…Although these studies demonstrated good initial response to therapy, they also showed that CR is unusual and serologic or clinical relapse between 12 and 24 months is common. [11][12][13][14] Since the early reports on long-term remissions of RA involved transplantation of allogeneic stem cells, several authors have postulated a graft-versus-autoimmunity effect (GvA) similar to the wellknown-graft-versus-leukemia (GvL) effect in hematological malignancies. [5][6][7] With the recent development of dosereduced conditioning regimens, the issue of allogeneic transplantation in RA became the subject of scientific discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies demonstrated good initial response to therapy, they also showed that CR is unusual and serologic or clinical relapse between 12 and 24 months is common. [11][12][13][14] Since the early reports on long-term remissions of RA involved transplantation of allogeneic stem cells, several authors have postulated a graft-versus-autoimmunity effect (GvA) similar to the wellknown-graft-versus-leukemia (GvL) effect in hematological malignancies. [5][6][7] With the recent development of dosereduced conditioning regimens, the issue of allogeneic transplantation in RA became the subject of scientific discussions.…”
Section: Discussionmentioning
confidence: 99%
“…9 In Chicago, four patients with RA have been treated with cyclophosphamide 200 mg/kg, ATG 90 mg/kg, methylprednisolone 3 g followed by a CD34 + cell enriched (2.5-2.7 log T-cell depleted) autograft. 16 Two of the four patients in this trial demonstrated sustained ACR 70 responses, whereas the remaining two were less successful. Likewise two patients in Omaha had ACR 70 responses until 6 months when disease recurrence occurred.…”
Section: Pilot Studiesmentioning
confidence: 85%
“…Following HCT, there was a somewhat better response to DMARDs supporting the immunomodulating effect of HCT. There has been variable success of HCT in RA, but the results have not been encouraging as compared to diseases like SSc or MS [87][88][89].…”
Section: Hct In Rheumatoid Arthritis and Juvenile Idiopathic Arthritismentioning
confidence: 99%